Increasing daily duration of rehabilitation for inpatients with sporadic inclusion body myositis may contribute to improvement in activities of daily living: A nationwide database cohort study - Takuaki Tani; Shinobu Imai; Kiyohide Fushimi (Medical Journals Sweden, 2023)
Objective: To analyse the association between the daily duration of rehabilitation for inpatients with sporadic inclusion body myositis and improvement in activities of daily living, using a Japanese nationwide inpatient administrative claims database. Methods: Data were extracted regarding inpatients with sporadic inclusion body myositis who had undergone rehabilitation between 1 April 2018 and 31 March 2021. The mean daily duration of rehabilitation was categorized into 2 groups: > 1.0 h (longer rehabilitation) and ≤ 1.0 h (shorter rehabilitation). The main outcome was improvement in activities of daily living from admission to discharge, measured using the Barthel Index. For the main analysis, a generalized linear model was used. Results: In total, 424 patients with sporadic inclusion body myositis met the eligibility criteria for inclusion in the study. The main analysis found a significant difference in improvement in activities of daily living between the longer rehabilitation and shorter rehabilitation groups after adjusting for confounders (risk ratio (95% confidence interval), 1.37 (1.06-1.78)). Conclusion: A longer daily duration of rehabilitation results in improved activities of daily living for inpatients with sporadic inclusion body myositis. LAY ABSTRACT Sporadic inclusion body myositis is a slowly progressive inflammatory myopathy. There is no known effective systemic therapy for sporadic inclusion body myositis; hence rehabilitation plays an important role in standard care for most patients. Although rehabilitation is currently provided to inpatients with the condition, there is almost no evidence for an association between the daily duration of rehabilitation and improvement in activities of daily living. The aim of this study was to evaluate the association between the daily duration of rehabilitation for inpatients with sporadic inclusion body myositis and improvement in activities of daily living, using a nationwide administrative database in Japan. The results show that a longer daily duration of rehabilitation results in improved activities of daily living for inpatients with sporadic inclusion body myositis.